2013
DOI: 10.1038/mi.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bacterial and anti-toxic immunity induced by a killed whole-cell-cholera toxin B subunit cholera vaccine is essential for protection against lethal bacterial infection in mouse pulmonary cholera model

Abstract: The lack of appropriate animal model for studying protective immunity has limited vaccine development against cholera. Here, we demonstrate a pulmonary cholera model conferred by intranasal administration of mice with live Vibrio cholerae. The bacterial components, but not cholera toxin, caused lethal and acute pneumonia by inducing massive inflammation. Intranasal immunization with Dukoral, comprising killed whole bacteria and recombinant cholera toxin B subunit (rCTB), developed both mucosal and systemic ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…It has been reported that Ca 2ϩ and Mg 2ϩ are necessary for full activation of the complement pathway to kill target bacteria because Ca 2ϩ and Mg 2ϩ are required for the C1 complex (C1r 2 C1s 2 ) and C4bC2 complex, respectively, in the classical complement activation pathway, which is an antibody-dependent pathway (23,24). In contrast, only Mg 2ϩ is required for activation of complement components (C3b-factorB) in the alternative pathway, an antibody-independent pathway, that is initiated by bacterial surface components and C3 (18,24,25). The results of this study showed that heparin did not affect vibriocidal antibody activity or anti-V. cholerae antibody titers in the plasma and serum samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Ca 2ϩ and Mg 2ϩ are necessary for full activation of the complement pathway to kill target bacteria because Ca 2ϩ and Mg 2ϩ are required for the C1 complex (C1r 2 C1s 2 ) and C4bC2 complex, respectively, in the classical complement activation pathway, which is an antibody-dependent pathway (23,24). In contrast, only Mg 2ϩ is required for activation of complement components (C3b-factorB) in the alternative pathway, an antibody-independent pathway, that is initiated by bacterial surface components and C3 (18,24,25). The results of this study showed that heparin did not affect vibriocidal antibody activity or anti-V. cholerae antibody titers in the plasma and serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and plasma IgG, IgM, and IgA levels against lipopolysaccharide (LPS) of V. cholerae were measured by enzyme-linked immunosorbent assay (ELISA) as previously described (18). Briefly, 96-well plates (Nunc, Roskilde, Denmark) were coated with 100 l of 2.5 g LPS in PBS at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, whole bacteria present all their antigenic determinants, activating the innate and adaptive immune response [12]. Additionally, phagocytosis and the complement system are activated, together with the formation of secretory IgA antibodies and the synthesis of cytokines, interferon alpha and gamma and T-type cellular responses [13].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the pulmonary infection with V. cholerae induces acute pneumonia leading to mouse death that mimics cholera in humans, and that it could be a useful animal model for pre-clinical evaluation of cholera vaccines [15]. However, the broad spectrum of protein expression in response to V. cholerae has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…Even though neonatal and germ-free animal models have been proposed, no animal models accurately recapitulate cholera pathogenesis [14]. To assess V. choleraeinduced acute inflammatory responses and the protective immunity induced by cholera vaccines, a pulmonary infection model has been developed [12,15]. The pulmonary infection model has advantages over the previously proposed animal models due to several common features: First, the respiratory tract has epithelial cells that contain brush-like cells as observed in the gastrointestinal tract [16], and both tracts are constantly exposed to external environments containing microbes [17].…”
Section: Introductionmentioning
confidence: 99%